New transliteration program “COTOGWA” development - Surynovych, Olena; Lishchyna, Nataliia; Lohatskyi, Vladyslav; Savluk, Maksym; Ryzhok, Solomiia (Odesa, 2024)
The purpose of the work is to develop a program for transliteration and refactoring of mechanically typed text “CotoGwa”. A literary analysis of the research problem is presented. The choice of ways, technologies and means of solving the task is substantiated. The functional and structural scheme of the program is substantiated. The process of developing a software product is highlighted. Comparative characteristics of analogues are carried out and their shortcomings are described. The advantages of the developed product are defined too. The oftware development model and used scientific research methods are justified. The practical application of the created product is described step by step. Testing and debugging of the program is described. Considering the implementation of the software, the architectural solutions and technologies used in the project were analyzed. The program takes into account the needs of users and can be easily extended to provide additional functionality thanks to the flexibility and extensive functionality of the C# programming language. In the future, the development of the program will include additional options to create even greater convenience and speed of use by users. Taking into account feedback from users can contribute to the further development of this software in the field of text printing. In general, the development makes it possible to efficiently and conveniently enter and edit text, reducing time spent on additional printing principles and facilitating routine tasks for users.
Keywords: computer program; object-oriented programming (OOP); cross-platform; encapsulation; polymorphism; inheritance; programming; C#